Emerging therapeutic targets for osteoporosis. (1st February 2020) - Gennari, Luigi; Merlotti, Daniela; Falchetti, Alberto; Eller Vainicher, Cristina; Cosso, Roberta; Chiodini, Iacopo
ABSTRACT: Introduction : Osteoporosis is a chronic, skeletal disorder characterized by compromised bone strength and increased fracture risk; it affects 50% of women and 20% of men. In the past two decades, there have been substantial improvements in the pharmacotherapy of osteoporosis which have yielded potent inhibitors of bone resorption or stimulators of bone formation. Areas covered : This review discusses newly identified targets and pathways and conceptual approaches to the prevention of multiple age-related disorders. Furthermore, it summarizes existing therapeutic strategies for osteoporosis. Expert opinion : Our enhanced understanding of bone biology and the reciprocal interactions between bone and other tissues have allowed the identification of new targets that may facilitate the development of novel drugs. These drugs will hopefully achieve the uncoupling of bone formation from resorption and possibly exert a dual anabolic and antiresorptive effect on bone. Alas, limitations regarding adherence, efficacy on nonvertebral fracture prevention and the long-term adverse events still exist for currently available therapeutics. Moreover, the efficacy of most agents is limited by the tight coupling of osteoblasts and osteoclasts; hence the reduction of bone resorption invariably reduces bone formation, and vice versa. This field is very much 'a work in progress.'